1995
DOI: 10.1182/blood.v86.4.1493.bloodjournal8641493
|View full text |Cite
|
Sign up to set email alerts
|

Local suppression of Epstein-Barr virus (EBV)-specific cytotoxicity in biopsies of EBV-positive Hodgkin's disease

Abstract: Epstein-Barr virus (EBV)-positive Hodgkin's and Reed-Sternberg (HRS) cells express the virus-encoded latent membrane proteins LMP1 and LMP2 that could serve as rejection targets in Hodgkin's disease (HD). To examine whether EBV-triggered reactivities can be detected in the tumor, we have compared cytokine mRNA expression, cell phenotype, and cytotoxic activity in biopsies from 8 EBV-carrying and 6 EBV-HD patients. Neither the pattern of lymphokine production nor the cell phenotype of the in vivo-activated inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…If HD patients are too immunocompromised to react against LMP-1, why do they not develop EBV-positive immunoblastomas, as seen in transplant recipients (Klein, 1992)? A possible explanation could be that EBV-specific cytotoxicity is suppressed locally in tumor tissue in EBV-positive patients, as reported by Frisan et al (1995). The mechanism behind this phenomenon, however, is unknown.…”
Section: Discussionmentioning
confidence: 86%
“…If HD patients are too immunocompromised to react against LMP-1, why do they not develop EBV-positive immunoblastomas, as seen in transplant recipients (Klein, 1992)? A possible explanation could be that EBV-specific cytotoxicity is suppressed locally in tumor tissue in EBV-positive patients, as reported by Frisan et al (1995). The mechanism behind this phenomenon, however, is unknown.…”
Section: Discussionmentioning
confidence: 86%
“…Elderly individuals are recognized to have lower immunocompetence than younger people. Elderly individuals may therefore have more difficulty in controlling the growth of an EBV-associated tumour than younger patients (Frisan et al, 1995;Armstrong et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This substantial immunomodulating activity might be of relevance at least in the neighbourhood of reactivating cells. For EBV-pos cases of Hodgkin's disease, for example, it has been shown that the tumour cells secrete high levels of IL-10 leading to suppression of local immunity [24].…”
mentioning
confidence: 99%